Nucleator-dependent intercellular assembly of adhesive curli organelles in Escherichia coli. - Hammar, M (1996)
Bacterial adhesion to other bacteria, to eukaryotic cells, and to extracellular matrix proteins is frequently mediated by cell surface-associated polymers (fimbriae) consisting of one or more subunit proteins. We have found that polymerization of curlin to fimbriae-like structures (curli) on the surface of Escherichia coli markedly differs from the prevailing model for fimbrial assembly in that it occurs extracellularly through a self-assembly process depending on a specific nucleator protein. The cell surface-bound nucleator primes the polymerization of curlin secreted by the nucleator-presenting cell or by adjacent cells. The addition of monomers to the growing filament seems to be driven by mass action and guided only by the diffusion gradient between the source of secreted monomer and the surface of monomer condensation.